The Significance of Aptitude Tests in the Selection of Prospective Music Teachers - Sülün, Erkan (Journal of History Culture and Art Research, 2017)
In Turkey and North Cyprus, music education departments are usually situated in faculties of education. The eligibility requirements are in two stages: Applicants who manage to attain the required minimum grade from Transition to Higher Education Examination can then take an aptitude test. These aptitude tests are designed by each university department to assess applicants’ qualifications. The main objective of this study is to examine the content and the structure of the aptitude test, and accordingly to be able to shed a light on the correlation between students’ aptitude tests scores and music and pedagogy course grades. For this purpose, the scores of 29 students who successfully passed the aptitude test in the Music Education Programme at Eastern Mediterranean University are compared with their course grades. This study employs quantitative descriptive research with an inter-relational sub-model. The Pearson correlation coefficient is used whilst analysing the relationship. The sampling method has been chosen for purposive sampling. This study determines both the content and predictive validity of the Music Education Department’s aptitude test.